Postoperative Complications Associated with External Skeletal Fixators in Dogs - Beever, Lee James; Giles, Kirsty; Meeson, Richard Lawrence (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives To quantify and evaluate risks of complications attributable to external skeletal fixator (ESF) usage in dogs.Methods A retrospective review of medical records following ESF placement.Results Case records of 97 dogs were reviewed; fixator-associated complications occurred in 79/97 dogs. Region of ESF placement was significantly associated with complication development (p = 0.005), not complication type (p = 0.086). Complications developed most frequently in the tarsus (9/10), manus (8/9) and humerus (8/9). Superficial pin-tract infection and implant failure occurred in 38/97 and 17/97 dogs, respectively. Superficial pin-tract infection occurred frequently in the femur, humerus, radius and ulna and the pes, with implant failure frequent in the tarsus and deep pin-tract infection in the manus and tibia. Transarticular frames were significantly more likely to develop a complication (p = 0.028). Age was significantly associated with complication development (p = 0.029). No associations between breed, sex, weight, fracture type (open or closed), ESF classification and the incidence or type of complications were identified. No associations between, breed, age, sex, weight, fracture type (open or closed), ESF classification and the time to complication development were identified.Clinical Significance Fixator-associated complications are common in dogs, with the majority of complications related to implant infection. Region and placement of transarticular frames should be carefully considered when selecting stabilization method.
Keywords: external fixator; postoperative complication; dog; canine